Near field communication - Want, R. (IEEE pervasive computing, 2011)
For many years, pervasive computing research has explored the potential benefits of creating a connection between the virtual world of the Internet, and the physical world we live in. The Near Field Communication (NFC) standard might, at last, be the technology that makes this vision-sometimes referred to as the Internet of things-a ubiquitous reality.